Current Approach to Phototherapy Applications in Dermatology Practice: Part 2. Phototherapy in Vitiligo, Mycosis Fungoides, Atopic Dermatitis, Sclerosing Diseases and Psoriasis - SEÇKİN GENÇOSMANOĞLU, DİLEK (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Many skin diseases can be treated with phototherapy, however, the method choice depends on the disease's characteristics. First-line phototherapy for generalized plaque psoriasis is narrowband ultraviolet B whereas it is psoralen and ultraviolet A for plaque stage mycosis fungoides and ultraviolet A1 for severe localized scleroderma. In this review, efficacy of different phototherapy methods in the most common diseases treated with phototherapy such as vitiligo, mycosis fungoides, atopic dermatitis, sclerosing diseases and psoriasis will be discussed in light of current guidelines.
Keywords: Atopic dermatitis; phototherapy; mycosis fungoides; psoriasis; scleroderma; vitiligo; NARROW-BAND-UVB; ULTRAVIOLET-B PHOTOTHERAPY; CHRONIC PLAQUE PSORIASIS; MONOCHROMATIC EXCIMER LIGHT; PSORALEN PLUS ULTRAVIOLET; MEDIUM-DOSE UVA1; AIR-CONDITIONED PHOTOTHERAPY; NONMELANOMA SKIN-CANCER; LYMPHOMA TASK-FORCE; DOUBLE-BLIND TRIAL